Characterization of sustainable building materials obtained from textile waste: From laboratory prototypes to real-world manufacturing processes. (1st March 2023) - Rubino, Chiara; Liuzzi, Stefania; Stefanizzi, Pietro; Martellotta, Francesco
Abstract: The limited availability of natural resources and the environmental impacts related to their extraction are the main reasons for developing construction materials using industrial residues as raw materials. On the other hand, the growing attention to the well-being of building occupants encourages the scientific community in proposing strategies not only sustainable, but also able to improve both the indoor acoustic and thermal comfort. The present work proposes nonwoven materials differing in density and thickness, obtained from textile waste, following an airlaying industrial process. The acoustic and thermal performances of the developed materials were investigated. Air flow resistivity was lower than 100 kN s/m 4 resulting in diffuse sound absorption coefficients higher than 0.6 starting from 500 Hz for 2.5 cm thick panels. A detailed characterization of the damping properties of the prepared samples (i.e. a total dynamic stiffness ranging from 7 to 13 MN/m 3 and an average loss factor ranging from 0.22 to 0.27), made it possible to model the sound insulation behaviour, proving significant improvements when the materials were applied as resilient layers in a floating floor or as insulating material in opaque façades. Furthermore, all the tested nonwovens showed a thermal conductivity lower than 0.05 W/(m·K), representing a good solution for the improvement of the energy efficiency of the building envelope. Highlights: Nonwovens made from textile waste were produced following an airlaying process. All the samples were tested in terms of thermal, acoustic and elastic properties. Measured thermal conductivity was lower than 0.06 W/(m·K) for all samples. Promising normal and random sound absorption coefficients were obtained. The nonwovens showed damping properties to be used for improving sound insulation.